A Bio-Psychosocial Framework for Chronic Daily Headaches: A Mixed Methods Study. (November 2021) - Balasubramanian, Bhuvaneshwari; Nair, Vasundharaa. S.; George, Nimmy; Reddy, Ashok V.; Thomas, Priya Treesa; Kulkarni, Girish B.
Chronic daily headaches (CDH) are primarily understood from a psychophysiological formulation. A broad biopsychosocial understanding, where there is equal importance given to biological, psychological and socio-cultural factors, is underexplored in headache. Socio-cultural factors, such as gender, socio-economic factors can perpetuate and worsen the condition. For an effective and sustainable intervention, these factors need to be considered. The current study aims to explore and develop a biopsychosocial framework for headache disorders. A convergent parallel mixed methods design was used and participants were recruited from a tertiary referral care hospital, Bengaluru, India. Headache Assessment Sheet, GAD 7, HDRS, PSS and B COPE were used in the quantitative phase. The data was analysed using r software. Qualitative phase of the study, in depth interview guide was used and data analysed thematically. Quantitative phase, 38 participants were recruited. The average age, was 38.02 (±10.17), majority of the participants being females 31 (81.58%). The mean duration of illness was 8.63 (±4.73) years. The anxiety scores positively correlated with pain intensity (r = 0.50 at P ≤ .001) and the median anxiety scores varied with photophobia ( P ≤ .03). The anxiety scores correlated with PSS (r = 0.428 at P ≤ .007) and HDRS (r = 0.428 at P ≤ .007) scores. Gender variations in coping were seen, avoidant coping having higher median scores in women. ( P ≤ .08). In qualitative phase of the study, six participants were recruited. Three main themes emerged from the qualitative phase of the study: headache - an illness, headache factors and the impact. Chronic daily headaches are influenced by biological, psychological, environmental and socio-cultural factors. A bio-psychosocial framework will help to understand and develop targeted interventions.